Education and Growth with Learning by Doing - Gabriele Marconi; Andries de Grip (Institute for the Study of Labor (IZA), 2015)
We develop a general equilibrium overlapping generations model which is based on the view that education makes workers more productive by increasing their ability to learn from work experience, rather than providing skills that directly increase productivity. One important implication of the model is that the enrolment rate to education has a negative effect on the GDP in the medium term and a positive effect in the long term. This could be an explanation for the weak empirical relationship between education and economic growth that has been found in the empirical macroeconomic literature. Conversely, for a given enrolment rate, the quality of education, as measured by workers' ability to learn, has a positive effect on the GDP both in the medium and in the long term.
Keywords: I25; J24; O11; O41; 330; education; learning-by-doing; productivity; economic growth; overlapping generations model